1991
DOI: 10.1113/expphysiol.1991.sp003551
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of blood‐brain and blood‐nerve barriers in experimental diabetes mellitus in the anaesthetized rat

Abstract: SUMMARYDiabetes was induced with streptozotocin in rats weighing about 160 g. These were maintained with age-matched controls for up to 14 months, blood glucose being periodically monitored. Half the diabetic and control rats received the aldose reductase inhibitor, Ponalrestat, in their diet. At 3 weeks, 6-7 months and 13-14 months, the vascular permeability in regions of brain, and in optic and sciatic nerves, were measured by maintaining radiotracers in the bloodstream -'l25-albumin (100 min), [14C]sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The human study suggests such might not be the case. Indeed, in rats treated with STZ, though some reports indicate physical BBB disruption can occur as early as 14-28 days after STZ injection for small molecules like sucrose (12,32), other studies offer data providing little indication of BBB disruption (for mannitol or sucrose) in rats treated with STZ as long as 9 or 14 months earlier (33,34). It seems that diabetes affects the BBB differently for different molecules (35).…”
Section: Discussionmentioning
confidence: 99%
“…The human study suggests such might not be the case. Indeed, in rats treated with STZ, though some reports indicate physical BBB disruption can occur as early as 14-28 days after STZ injection for small molecules like sucrose (12,32), other studies offer data providing little indication of BBB disruption (for mannitol or sucrose) in rats treated with STZ as long as 9 or 14 months earlier (33,34). It seems that diabetes affects the BBB differently for different molecules (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific effects of diabetes on the blood-brain barrier (BBB) remain controversial. Studies utilizing the streptozotocin (STZ)-induced model of diabetes to assess its effect on the BBB have indicated that the BBB remains intact [4], whereas recent work [29] indicates that BBB permeability is increased in STZ diabetes. Clinical studies of BBB function in diabetes have been similarly disparate [7,38].…”
Section: Introductionmentioning
confidence: 99%
“…These endothelial cells are distinguishable from other endothelial cell beds by a number of characteristics; they have very low levels of transcellular endocytosis, express specific ion and peptide transporters in a polarized manner, and form a low permeability physical barrier between the blood and the brain due to the presence of tight junctions between adjacent endothelial cells [34,63,74]. The barrier function of the BBB can be disrupted by a number of different stimuli or pathophysiologies, including hyperosmolar-induced cell shrinkage [22,92], hypoxic stress and stroke [5,23,98], Alzheimer's disease [70,88], diabetes [13,19], multiple sclerosis [58,111] and inflammatory pain [20,65].…”
Section: Introductionmentioning
confidence: 99%